The last child - Hart, John, 1965- (New York : Minotaur Books, 2009)
After his twin sister Alyssa disappears, thirteen year-old Johnny Merrimon is determined to find her.
Keywords: Missing children -- Fiction; Twins -- Fiction; North Carolina -- Fiction; Psychological fiction; Mystery fiction